“Bestial People”: Moral Exempla in Sermons by Symeon of Polotsk - Preobraženskaja [Anastasija Preobraženskaja], Anastasija (Jezikoslovni zapiski, 2018)
This article examines animal exempla included in two sermon collections: Obed dushevnyi (Spiritual Lunch) and Vecherya dushevnaia (Spiritual Dinner) by the first Moscow court poet and preacher Symeon of Polotsk (1629–1680). The possible origins of animal exempla, their function in sermons, patterns of exempla, and their relation to original texts and scripture are discussed. An attempt is made to show Symeon’s original work using borrowed texts.